2012
DOI: 10.1128/aac.00432-10
|View full text |Cite
|
Sign up to set email alerts
|

VraSR Two-Component Regulatory System Contributes to mprF -Mediated Decreased Susceptibility to Daptomycin in In Vivo -Selected Clinical Strains of Methicillin-Resistant Staphylococcus aureus

Abstract: Daptomycin (DAP) is a new class of cyclic lipopeptide antibiotic highly active against methicillin-resistant Staphylococcus aureus (MRSA) infections. Proposed mechanisms involve disruption of the functional integrity of the bacterial membrane in a Cadependent manner. In the present work, we investigated the molecular basis of DAP resistance in a group of isogenic MRSA clinical strains obtained from patients with S. aureus infections after treatment with DAP. Different point mutations were found in the mprF gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
118
1
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(134 citation statements)
references
References 48 publications
5
118
1
7
Order By: Relevance
“…Decreased susceptibility to DAP in S. aureus has been reported to lead to clinical failures in patients with MRSA deep-site infections, such as endocarditis and abscesses (28)(29)(30). Previously, we identified two major factors that mutually cooperate in the acquisition of DAP resistance; one is related to the cell membrane (mrpF mutations), and the second affects cell wall factors (VraSR) (6). Moreover, we observed that the DAP r phenotype was accompanied by increased susceptibility to OXA, the so-called seesaw effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Decreased susceptibility to DAP in S. aureus has been reported to lead to clinical failures in patients with MRSA deep-site infections, such as endocarditis and abscesses (28)(29)(30). Previously, we identified two major factors that mutually cooperate in the acquisition of DAP resistance; one is related to the cell membrane (mrpF mutations), and the second affects cell wall factors (VraSR) (6). Moreover, we observed that the DAP r phenotype was accompanied by increased susceptibility to OXA, the so-called seesaw effect.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of all PCR amplification products was performed at the Nucleic Acid Research Facility at Genewiz (South Plainfield, NJ). Analysis of the mprF sequence in wild-type strains and mutants was performed by using mprF-specific primers as previously described (6). Consensus sequences were assembled from both orientations with Lasergene (v12) software (DNAStar, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Otro sistema regulador de dos componentes relacionado con el desarrollo de la resistencia a la daptomicina es el vraSR (también relacionado con el desarrollo de S. aureus de sensibilidad intermedia a la vancomicina), el cual se ha encontrado sobreexpresado en cepas resistentes a la daptomicina. Aún más, la inactivación de estos genes en dichas cepas revierte la sensibilidad a este antibiótico (101). Por último, los genes vraF (proteína transportadora de tipo ABC) y vraG (proteína transportadora de tipo permeasa) también han sido asociados con el desarrollo de resistencia a la daptomicina en S. aureus (102).…”
Section: Resistencia a La Daptomicina En Staphylococcus Aureusunclassified